2010
DOI: 10.1002/pola.24431
|View full text |Cite
|
Sign up to set email alerts
|

Controlled grafting of cellulose esters using SET‐LRP process

Abstract: Here, we present the first example of application of single-electron transfer living radical polymerization (SET-LRP) process to a controlled grafting of cellulose esters, cellulose diacetate (CDA), and cellulose acetate butyrate (CAB). The cellulose ester macroinitiators with various functionality densities have been prepared by acylation of the backbones with 2-bromoisobutyryl (BrIB) and dichloroacetyl (DCA) groups, respectively. Methacrylate monomers were polymerized using DCA-functionalized macroinitiators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 48 publications
(68 reference statements)
4
21
0
Order By: Relevance
“…3), indicating that the polymerization proceeded under controlled/“living” conditions. This agrees with the results reported by Vlcek et al,30 who found that the grafting of (meth)acrylate monomers onto cellulose esters via SET‐LRP could be realized in a well‐controlled manner. Very recently, Nguyen et al found that 2‐bromoisobutyric acid could give improved control over molecular weight evolution in the SET‐LRP of methyl acrylate than its counterpart of 2‐bromopropionate 31.…”
Section: Resultssupporting
confidence: 92%
“…3), indicating that the polymerization proceeded under controlled/“living” conditions. This agrees with the results reported by Vlcek et al,30 who found that the grafting of (meth)acrylate monomers onto cellulose esters via SET‐LRP could be realized in a well‐controlled manner. Very recently, Nguyen et al found that 2‐bromoisobutyric acid could give improved control over molecular weight evolution in the SET‐LRP of methyl acrylate than its counterpart of 2‐bromopropionate 31.…”
Section: Resultssupporting
confidence: 92%
“…3), indicating that the polymerization proceeded under controlled/''living'' conditions. This agrees with the results reported by Vlcek et al, 30 who found that the grafting of (meth)acrylate monomers onto cellulose esters via SET-LRP could be realized in a well-controlled manner. Very recently, Nguyen et al found that 2-bromoisobutyric acid could give improved control over molecular weight evolution in the SET-LRP of methyl acrylate than its counterpart of 2-bromopropionate.…”
Section: Synthesis Of Cs-poegmasupporting
confidence: 93%
“…Radical polymerization is by far the most used method for grafting of cellulose, and numerous examples can be found in the literature. These use either traditional redox initiators6, 7 or exploit modern methods of controlled radical polymerization, such as nitroxide‐mediated polymerization,8 radical addition‐fragmentation chain transfer,9 single‐electron transfer living radical polymerization (SET‐LRP)10 and, in particular, atom transfer radical polymerization (ATRP) 11–13. The ATRP and SET‐LRP methods allow for an extensive control over the copolymer architecture by introduction of initiation sites into the cellulose chains in the first step, giving rise to a macroinitiator, followed by polymerization of a chosen monomer in the second step.…”
Section: Introductionmentioning
confidence: 99%